Wind drift explains the reoriented morning flights of songbirds. (28th February 2016) - Van Doren, Benjamin M.; Horton, Kyle G.; Stepanian, Phillip M.; Mizrahi, David S.; Farnsworth, Andrew
Lay Summary: Nocturnally migrating birds over the northeast United States face winds that can push them out to sea; many respond with morning corrective flights. In this study, we unite novel analyses of weather radar data and traditional, ground-based visual observations to paint a clearer picture of birds' interactions with winds. Our results illustrate how the behaviors and strategies animals employ during long-distance migrations are intricately connected to the conditions they experience en route. Abstract: Remote sensors such as Doppler radars are providing novel insights into the migrations of diverse animal taxa, but limits in scope and sensitivity can hamper the utility of these tools. For example, studies investigating whether songbirds compensate effectively for wind displacement during nocturnal migration have been challenged by the need to assess behavior on a large scale. In addition, these studies typically overlook the potential role low-altitude diurnal flights play in dealing with unfavorable winds. In such cases, a combination of approaches—new and traditional—may be necessary to understand behavior more completely. Here, we unite ground-based visual observations with a new radar analysis method to investigate how songbirds deal with crosswinds over the northeast United States. We find that nocturnally migrating birds experienced significant wind drift, even though they often flew at 90° or more to the wind direction. Significantly, more birds undertook reoriented diurnal flights after nocturnal wind drift, and wind influence, nocturnal migration intensity, and time of season together explained the majority of variation in counts of these "morning flights." This study shows that bird behavior during migration can be strongly shaped by the danger of wind drift and that some songbird species respond to drift with reoriented diurnal migratory flights. Knowledge of birds' interactions with wind is essential for successfully modeling migratory behavior and assessing the risks associated with changing habitats and meteorological patterns. Furthermore, an understanding of the degree to which drift defines migratory behaviors may have value across animal taxa.